Green Belts and Coastal Risk Management - Shaw, Rajib; Noguchi, Yusuke; Ishiwatari, Mikio (World Bank, Washington, DC, 2013)
For more than four centuries Japan has been developing forested green belts to mitigate coastal hazards such as sandstorms, salty winds, high tides, and tsunamis. Although Japan's green belts were severely damaged by the March 11 tsunami, they did reduce the impact of waves, and protected houses by capturing floating debris. Local governments are planning to reconstruct the green belts as a countermeasure against tsunamis. While local communities have traditionally taken charge of maintaining green belts, their role has been weakened because of changes in society brought about by economic development and urbanization. The people who lived on the dunes along the coast had suffered from sandstorms and tidal disasters that damaged their agricultural products and the pine forests protected their fields. Masamune allowed the people to sell wood from branches that were trimmed or had fallen to cover the expense of maintaining the green belt. The green belt became less important after the rapid economic growth of the 1970s, as other more effective Disaster Risk Management (DRM) measures were developed, and electricity and gas replaced wood as energy sources for people. The community's role in managing the green belt diminished, and governments took over its maintenance.